EDUCATION ON THE IMPORTANCE OF MAINTAINING BLOOD SUGAR LEVELS - Tysa Runingsari; nikita welandha (ABDIMASNU: Jurnal Pengabdian kepada Masyarakat, 2025)
Background : Diabetes is a disease that if No handled with appropriate will cause complications more continued . Diet and food selection material the right food can help control disease This . Lack of knowledge related diabetes mellitus disease and foods that must be consumed consumed make factor main activity This done . Method: Activity This done with giving education and cooking demonstration material local For diabetes mellitus disease in Gemulung Village with amount 22 participants . Result: There is improvement knowledge from results giving education and cooking demonstration related diabetes mellitus disease . Examination results glucose blood when showed 3 people with diabetes, 1 person with pre-diabetes, and 18 people with normal category . Conclusion : Improvement knowledge about diabetes mellitus can done with method giving education and cooking demonstrations . Required effort sustainable in order to be able to prevent diabetes mellitus disease .